Alice nel paese dei Photomaton: Wim Wenders e l’autoritratto fotografico - Amigoni, Ferdinando (Status Quaestionis, 2022)
Since the 1920s, when it appeared in railway stations and on urban crossroads, the photo- booth has managed to capture the attention of both laymen and artists. The catalogue of artists – painters, writers, photographers, installation and performance creators, as well as film and theatre directors – who were bowled over by this mysterious machine is teeming with names. Nonetheless, its huge success in the early 70s leaves one somewhat astounded. The place of honour goes to Franco Vaccari, who created, for the 1972 Biennale di Venezia, the work Esposizione in tempo reale, which he then followed up in his operation Photomatic d’Italia. Amongst the many noteworthy works, Wim Wenders’s early films stand out, in which, with notable regularity, Photomatic is cited as marvelous image producing machine. This essay will focus on the sequence dedicated to a photobooth in Alice in the Cities: sur- prising analogies, both in their theoretical elaboration and in their poetic praxis, justify the juxtaposition between the German director and the Italian conceptual artist, not without duly glancing at the philosophical hypotheses of Heidegger’s later work.